Effect of Some Egg Quality Traits on Hatching Results in Brown Pure Lines - İsmail Durmuş; Serdar Kamanlı; Sezai Alkan (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to determine the influence of eggshell thickness, albumen height, yolk height and haugh unit on hatching results. A total of 746 eggs, which were obtained and evaluated for egg quality parameters from 100 brown pure line hens of 42 weeks of age, were used. Eggs were collected from each hen for 12 days and individual incubation was carried out. Eggs were grouped based on quality parameters and evaluated accordingly. The findings suggested that hatchability, hatchability of fertile eggs, early, mid and late embryonic mortality did not differ in terms of haugh unit, albumen height, eggshell thickness and yolk height groups. However, early embryonic mortality was found different between the yolk height groups. No relationship was determined among albumen height, haugh unit, eggshell thickness and hatching results. There was no relation between yolk height and hatchability of fertile eggs, hatchability, mid and late embryonic mortalities but was a positive correlation with early embryonic mortality. The results of the present study demonstrate that egg quality parameters studied here had no influence on hatching results except that early embryonic mortality increased with the yolk height.